2011
DOI: 10.1080/00071668.2011.606800
|View full text |Cite
|
Sign up to set email alerts
|

Effects of organically-complexed minerals on meat quality in chickens

Abstract: The impact of combined lower concentrations of organically-complexed versus inorganic copper, zinc and manganese on meat quality in chickens was investigated. A total of 200 male broiler chicks (Ross-308), 1-d-old and weighing approximately 40 g, were divided into 4 groups comprising three experimental groups and one control group, with each consisting of 50 chicks. All groups were also divided into 5 subgroups, with each containing 10 broiler chicks. All birds were given a starter diet from d 1 to d 21, and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
24
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(29 citation statements)
references
References 21 publications
5
24
0
Order By: Relevance
“…Statistically, the pHU and WHC were not significantly influenced by combined Zn/Cu complexes, yet WHC values were still higher in the tested treatments than in the control. This was partially in accordance with the results of [55], who used different dietary Zn and Cu forms in poultry. Additionally, drip loss 24h and drip loss 48h percentages generated from supplemented rabbits were close to those in the controls and seems to be rather constant (p > 0.05).…”
Section: Discussionsupporting
confidence: 91%
“…Statistically, the pHU and WHC were not significantly influenced by combined Zn/Cu complexes, yet WHC values were still higher in the tested treatments than in the control. This was partially in accordance with the results of [55], who used different dietary Zn and Cu forms in poultry. Additionally, drip loss 24h and drip loss 48h percentages generated from supplemented rabbits were close to those in the controls and seems to be rather constant (p > 0.05).…”
Section: Discussionsupporting
confidence: 91%
“…Zinc has been found to inhibit endogenous as well as exogenous lipid peroxidation in both in vivo and in vitro conditions (Chvapil et al, 1973) and thus increased SOD activity there by leading to increased catalase concentration (Clemen and Waller, 1987). Similar to our findings Aksu et al (2011) reported that supplementation of Zn-methionine decreased lipid peroxidation in the chickens by lowering the plasma levels of MDA.…”
Section: Blood Biochemicalssupporting
confidence: 81%
“…The sequence of chicken response to MDA content of meat from highest to lowest was found in treatment combination of LA feed without supplementation, LA supplemented by AV at a dose of 625 mg.kg MDA is one of the indicators of lipid peroxidation in the body which is often used in association with oxidative stress (Aksu et al, 2011). The compound can cause damage to cell components, such as lipids, proteins, and nucleic acids.…”
Section: Lipids Oxidation Products Of Broiler Meatmentioning
confidence: 99%